Modelling and Simulation of DC Motor Speed Control Using Fuzzy-PID Algorithm - Anrico Gideon Alfano; Hari Maghfiroh; Irwan Iftadi; Chico Hermanu B.A.; Feri Adriyanto (Journal of Electrical, Electronic, Information, and Communication Technology, 2019)
This paper discusses the simulation of the Fuzzy-PID hybrid algorithm as a method for controlling the speed of a DC motor compared to the usual PID method. Comparisons were also made to the membership functions used in the fuzzy logic fuzzification process. Membership functions that are used are triangular, trapezoidal, and gaussian shaped function with each having 3, 5, and 7 as the number of membership to be compared. The performance of this control is compared by looking at the results of the step unit responses and the ability in tracking signals. The simulation results show that the Fuzzy-PID algorithm is superior to the ordinary PID algorithm but slower on computation time. The results of the comparison in the fuzzification process shows that the more number used in membership function, the faster the response reaches the set point, while the difference in shape has little effect on the response. The best results are achieved by fuzzy triangle shaped function with 7 membership number.